Liberia - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
The Debt Sustainability Analysis (DSA) suggests that Liberia remains at moderate risk of debt distress with limited space to accommodate shocks. The country’s debt carrying capacity remains medium, but the rating has declined from 3.1 to 2.77. The authorities have pursued non-concessional loans, but none has been disbursed yet. The government has instead borrowed U.S. dollars from the Central Bank of Liberia (CBL) to close the financing gap in FY2018. Such new borrowing, as well as the legacy U.S. dollar debt from the civil war time, are both incorporated in the new DSA. The State-owned Enterprises (SOE) guaranteed debt is also incorporated. Liberia will edge closer to high risk of debt distress with a small change in the terms of both domestic and external debt or a failure to adjust primary expenditure to the available revenue envelope over the medium-term.